Resin composition and application thereof
By using a resin composition of benzooxazine resin and epoxy resin containing allyl and benzocyclobutene structures in the copper clad plate, it is solved that it is difficult to achieve low dielectric constant and low dielectric loss factors in the prior art. , the problems of high heat resistance and low dimensional stability achieve better dielectric performance and heat resistance.
Patent Information
- Application Number
- CN202411508239.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The prior art is difficult to simultaneously achieve low dielectric constant, low dielectric loss factor, high heat resistance and low dimensional stability of the resin composition in copper clad plates.
Using a resin composition including benzoxazine resin and epoxy resin, a benzoxazine compound containing an allyl group and benzocyclobutene structure in the benzoxazine resin is used, and the ring opening and epoxy are opened by benzoxazine. The appropriate reaction of the base increases the cross-linking density and improves heat resistance.
The dielectric constant and dielectric loss of the resin composition are effectively reduced, heat resistance and dimensional stability are improved, and the problem of poor dielectric performance in copper clad plates is solved.
Smart Images

Figure CN119391132A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electronic materials, and in particular to a resin composition and application thereof. Background Art
[0002] With the rapid development of high-frequency communication technology, especially in the fifth-generation communication system "5G" which is being accelerated, in order to promote large-capacity and high-speed communication, the demand for low dielectric constant and low dielectric loss tangent materials is increasing. As an important component of electronic equipment, the performance of copper clad laminates is directly related to the performance of the entire device. Traditional copper clad laminates often have problems such as high dielectric constant and large thermal expansion coefficient during high-frequency and high-speed signal transmission. These problems will cause the leakage current of the integrated circuit to increase and heat up seriously, thus affecting the stability and life of the equipment. In this context, it is particularly important to study the use of benzoxazine resin as a material with excellent heat resistance and electrical properties, and to develop a resin composition with low dielectric and high heat resistance.
[0003] Benzoxazine resin has a small curing shrinkage rate during the polymerization reaction at high temperature, and the cured product has high heat resistance, high carbon residue rate and excellent thermal stability, so it is widely used in the field of copper clad laminates, but it has the disadvantage of poor dielectric properties. In the prior art, it is relatively difficult to achieve low dielectric constant (Dk), low dielectric loss factor (Df) and high heat resistance and low dimensional stability at the same time. For example, the combination of hydrocarbon and hollow filler has achieved low Dk and low Df, but because hydrocarbon has a long chain structure, the heat resistance and dimensional stability are significantly greater.
[0004] Epoxy resin has excellent mechanical properties, electrical properties, chemical properties, bonding properties, easy molding and processing, low cost and other advantages. In recent years, its application has been extended to structural adhesive materials, semiconductor packaging materials, fiber-reinforced materials, laminates, copper foil, integrated circuits and other electronic and electrical packaging materials. However, epoxy resin has a three-dimensional network structure, lacks sliding between molecular chains, has large internal stress, and is prone to cracking, deformation and other problems. Summary of the invention
[0005] The purpose of the present application is to provide a resin composition and its application, wherein the resin composition includes a benzoxazine resin and an epoxy resin, wherein the benzoxazine resin includes a benzoxazine compound with an allyl group and a benzocyclobutene structure, which can reduce the dielectric constant and the connection loss of the resin composition, thereby solving the problem of poor dielectric properties of the resin composition in the copper-clad laminate in the prior art.
[0006] In order to achieve one of the above-mentioned objects of the invention, an embodiment of the present application provides a resin composition, which comprises the following components by weight:
[0007] Benzoxazine resin: 1 to 80 parts by weight;
[0008] Epoxy resin: 20-100 parts by weight;
[0009] Curing agent: 5-50 parts by weight;
[0010] The benzoxazine resin contains the following structural formula (1a) or structural formula (1b):
[0011]
[0012] Wherein, Ar is methylene, ethylene, -O-, -S- or
[0013] As a further improvement of an embodiment of the present application, the benzoxazine resin further includes a benzocyclobutenyl-free benzoxazine resin. Based on 100 parts by weight of the benzoxazine resin, the benzocyclobutenyl-free benzoxazine resin comprises 10 to 80 parts by weight.
[0014] As a further improvement of one embodiment of the present application, the benzocyclobutenyl-free benzoxazine resin is selected from one or a combination of at least two of bisphenol A-type benzoxazine resin, bisphenol F-type benzoxazine resin, phenolphthalein-type benzoxazine resin, dicyclopentadiene-type benzoxazine resin, phosphorus-containing benzoxazine resin, diamine-type benzoxazine resin or allyl benzoxazine resin.
[0015] As a further improvement of one embodiment of the present application, the benzocyclobutenyl-free benzoxazine resin is at least one of the following structural formulas:
[0016] Wherein, R is vinyl, allyl, propenyl or methacrylate; Ar is methylene, ethylene, -O-、-S-、
[0017] or no linking group;
[0018] Wherein, Ar is methylene, ethylene, -O-、-S-、 or no linking group;
[0019] Wherein, R is vinyl, allyl, propenyl or methacrylate; Ar is methylene, ethylene, -O-、-S-、 Or no linking group.
[0020] As a further improvement of one embodiment of the present application, the epoxy resin is selected from any one of dicyclopentadiene epoxy resin, carbon-carbon double bond-containing epoxy resin, phosphorus-containing epoxy resin, isocyanate-modified epoxy resin, biphenyl epoxy resin, bisphenol A epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, epoxidized polybutadiene resin, naphthalene ring-containing epoxy resin, and bisphenol F epoxy resin, or a combination of at least two thereof.
[0021] As a further improvement of an embodiment of the present application, the epoxy resin is selected from at least one of the following structures:
[0022] Wherein, m is an integer from 0 to 10;
[0023] Wherein, n is an integer from 1 to 20;
[0024] Wherein, p is an integer from 1 to 20;
[0025] Wherein, n is an integer from 0 to 7, and R is H or -CH3;
[0026] Wherein, X1 is H or a C1-C5 alkyl group; X2 is H or a C1-C5 alkyl group;
[0027] Wherein, X1 is H or a C1-C5 alkyl group;
[0028] Wherein, n is an integer from 0 to 7, and R is -O- or -Co-.
[0029] As a further improvement of one embodiment of the present application, the curing agent is selected from at least one of an amine curing agent, an active ester curing agent, a phenolic curing agent, an acid anhydride curing agent, a maleimide curing agent, and a cyanate curing agent.
[0030] As a further improvement of an embodiment of the present application, the amine curing agent is selected from at least one of diaminodiphenylmethane, diaminodiphenyl sulfone, diethylenetriamine, dicarboxyphthalimide, dicyandiamide or imidazole;
[0031] The phenolic curing agent is selected from at least one of bisphenol A phenolic resin, phenol phenolic resin, naphthalene phenolic resin, biphenyl phenol phenolic resin, biphenyl phenol naphthol resin, and dicyclopentadiene phenol addition resin;
[0032] The acid anhydride curing agent is selected from at least one of phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, hydrogenated phthalic anhydride, nadic anhydride or styrene-maleic anhydride;
[0033] The cyanate curing agent is selected from at least one of bisphenol A cyanate, bisphenol F cyanate, bisphenol E cyanate, bisphenol M cyanate, DCPD cyanate, naphthalene cyanate, phenolic cyanate and biphenyl cyanate;
[0034] The active ester curing agent is a compound having the following structural formula:
[0035] Wherein, X is phenyl or naphthyl; j is 0 or 1; k is 0 or 1; and n represents a repeating unit, which is 0.25-1.25.
[0036] As a further improvement of one embodiment of the present application, it also includes 5 to 30 parts by weight of a flame retardant, wherein the flame retardant is selected from at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organosilicon flame retardant, and an organic metal salt flame retardant.
[0037] As a further improvement of an embodiment of the present application, the brominated flame retardant is selected from at least one of decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide;
[0038] The phosphorus-based flame retardant is selected from condensed phosphate esters, phosphoric acid, hypophosphite, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, (m is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphophanate-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene, modified phosphazene, wherein the structure of the DOPO group is
[0039] One embodiment of the present application also provides a use of the resin composition as described above in a prepreg, a laminate, an insulating film, an insulating board, a circuit substrate and an electronic device.
[0040] One or more technical solutions provided by this application have at least the following technical effects or advantages:
[0041] The resin composition provided in the present application includes a benzoxazine resin and an epoxy resin, wherein the benzoxazine resin contains a benzoxazine compound having an allyl group and a benzocyclobutenyl group, which reduces the dielectric constant and dielectric loss of the resin composition. During curing, the benzoxazine maintains a proper reaction with the epoxy group after ring opening, thereby increasing the crosslinking density and improving the heat resistance. DETAILED DESCRIPTION
[0042] The present invention will be described in detail below in conjunction with specific embodiments, but these embodiments do not limit the present invention, and changes in reaction conditions, reactants or raw material amounts made by ordinary technicians in the field according to these embodiments are all included in the protection scope of the present invention.
[0043] The present application provides a resin composition, which comprises the following components by weight:
[0044] Benzoxazine resin: 1 to 80 parts by weight;
[0045] Epoxy resin: 20-100 parts by weight;
[0046] Curing agent: 5-50 parts by weight;
[0047] The benzoxazine resin contains the following structural formula (1a) or structural formula (1b):
[0048]
[0049] Wherein, Ar is methylene, ethylene, -O-, -S- or
[0050] The resin composition provided in the present application comprises a benzoxazine resin and an epoxy resin, wherein the benzoxazine resin comprises a benzoxazine compound as shown in the above structural formula (1a) or structural formula (1b), wherein the compound has an allyl group and a benzocyclobutene group, and both structures can improve the dielectric properties of the resin composition. When the resin composition is cured, the benzoxazine ring opens and maintains a proper reaction with the epoxy group, thereby increasing the crosslinking density and further improving the heat resistance.
[0051] In some embodiments, the benzoxazine compound is obtained by reacting an allyl bisphenol compound, aminobenzocyclobutene and formaldehyde, wherein the molar ratio of the allyl bisphenol compound, aminobenzocyclobutene and formaldehyde is 1:(2-6):(1-3). The reaction temperature of the allyl bisphenol compound, aminobenzocyclobutene and formaldehyde is 50-100° C., and the reaction time is 1-15 hours.
[0052] In some embodiments, the allyl bisphenol compound is represented by structural formula (1c) or structural formula (1d):
[0053] Wherein, Ar is methylene, ethylene, -O-, -S- or
[0054]
[0055] When diallyl bisphenol A is selected as the allyl bisphenol compound, Ar in the structural formula (1a) and the structural formula (1c) is When the allyl bisphenol compound is diallyl bisphenol methane, Ar in the structural formula (1a) and the structural formula (1c) is a methylene group; when the allyl bisphenol compound is diallyl bisphenol ethane, Ar in the structural formula (1a) and the structural formula (1c) is an ethylene group; when the allyl bisphenol compound is diallyl bisphenol S, Ar in the structural formula (1a) and the structural formula (1c) is When the allyl bisphenol compound is diallyl phenyl ether, Ar in the structural formula (1a) and the structural formula (1c) is -O-. Preferably, the allyl bisphenol compound is diallyl bisphenol A.
[0056] In some embodiments, a catalyst is added during the reaction of the allyl bisphenol compound, aminobenzocyclobutene and formaldehyde, and the amount of the catalyst added is 0.01-2% of the total weight of the allyl bisphenol compound, aminobenzocyclobutene and formaldehyde.
[0057] In some embodiments, the catalyst is one or a mixture of two or more of zinc chloride, indium trihalide, ferric chloride, antimony pentachloride, trifluoromethanesulfonate, morpholine trifluoroacetate, aluminum trichloride-nitroalkyl complex, wherein the halogen in the indium trihalide includes F, Cl, Br, and I.
[0058] In some embodiments, the benzoxazine resin further includes a benzocyclobutenyl-free benzoxazine resin. Based on 100 parts by weight of the benzoxazine resin, the benzocyclobutenyl-free benzoxazine resin comprises 10 to 80 parts by weight.
[0059] Preferably, the benzocyclobutenyl-free benzoxazine resin is selected from one or a combination of at least two of bisphenol A-type benzoxazine resin, bisphenol F-type benzoxazine resin, phenolphthalein-type benzoxazine resin, dicyclopentadiene-type benzoxazine resin, phosphorus-containing benzoxazine resin, diamine-type benzoxazine resin or allyl benzoxazine resin.
[0060] In some embodiments, the benzocyclobutenyl-free benzoxazine resin is at least one of the following structural formulas:
[0061] Wherein, R is vinyl, allyl, propenyl or methacrylate; Ar is methylene, ethylene, -O-、-S-、 or no linking group;
[0062] Wherein, Ar is methylene, ethylene, -O-、-S-、 or no linking group;
[0063] Wherein, R is vinyl, allyl, propenyl or methacrylate; Ar is methylene, ethylene, -O-、-S-、 Or no linking group.
[0064] The aforementioned “no connecting group” specifically means that the benzene rings on both sides of Ar are directly connected without being connected through other groups.
[0065] In some embodiments, the epoxy resin is selected from any one of dicyclopentadiene epoxy resin, carbon-carbon double bond-containing epoxy resin, phosphorus-containing epoxy resin, isocyanate-modified epoxy resin, biphenyl epoxy resin, bisphenol A epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, epoxidized polybutadiene resin, naphthalene ring-containing epoxy resin, and bisphenol F epoxy resin, or a combination of at least two thereof.
[0066] Preferably, the epoxy resin is selected from at least one of the following structures:
[0067] Wherein, m is an integer from 0 to 10;
[0068] Wherein, n is an integer from 1 to 20;
[0069] Wherein, p is an integer from 1 to 20;
[0070] Wherein, n is an integer from 0 to 7, and R is H or -CH3;
[0071] Wherein, X1 is H or a C1-C5 alkyl group; X2 is H or a C1-C5 alkyl group;
[0072] Wherein, X1 is H or a C1-C5 alkyl group;
[0073] Wherein, n is an integer from 0 to 7, and R is -O- or -Co-.
[0074] Preferably, the epoxy resin contains allyl groups. The aforementioned structural formula (1a) and structural formula (1b) contain allyl groups. When the allyl-containing epoxy resin is mixed with the allyl-containing benzoxazine, the compatibility between the two is very excellent. During the curing reaction, the larger benzocyclobutene is better introduced into the cross-linked network system, which can greatly improve the dielectric properties of the resin composition, reduce water absorption, and improve heat resistance.
[0075] The epoxy resin is selected from any one or more of the following grades of materials:
[0076] HP4032, HP4032D, HP4032SS, HP4700, HP4710, N-690, N-695, HP7200, HP7200H, HP7200HH, EXA7311, HP6000 produced by Japan DIC Corporation, NC3000, NC7000, NC3100 produced by Nippon Chemical, ESN475V, ESN485 produced by Nippon Steel Chemical, and MADGIC produced by Shikoku Chemical of Japan.
[0077] In some embodiments, the curing agent is selected from at least one of an amine curing agent, an active ester curing agent, a phenolic curing agent, an anhydride curing agent, a maleimide curing agent, and a cyanate curing agent.
[0078] Preferably, the amine curing agent is selected from at least one of diaminodiphenylmethane, diaminodiphenyl sulfone, diethylenetriamine, dicarboxyphthalimide, dicyandiamide or imidazole;
[0079] The phenolic curing agent is selected from at least one of bisphenol A phenolic resin, phenol phenolic resin, naphthalene phenolic resin, biphenyl phenol phenolic resin, biphenyl phenol naphthol resin, and dicyclopentadiene phenol addition resin;
[0080] The anhydride curing agent is selected from at least one of phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, hydrogenated phthalic anhydride, nadic anhydride or styrene-maleic anhydride;
[0081] The cyanate curing agent is selected from at least one of bisphenol A cyanate, bisphenol F cyanate, bisphenol E cyanate, bisphenol M cyanate, DCPD cyanate, naphthalene cyanate, phenolic cyanate and biphenyl cyanate;
[0082] The active ester compound is a compound having the following structural formula:
[0083] Wherein, X is phenyl or naphthyl; j is 0 or 1; k is 0 or 1; and n represents a repeating unit, which is 0.25-1.25.
[0084] More preferably, the curing agent is selected from active ester compounds. When the active ester group reacts with the epoxy group, no hydroxyl group with strong polarity is generated, which is beneficial to the improvement of the dielectric properties.
[0085] In some embodiments, the resin composition further comprises 5 to 60 parts by weight of an elastomer, wherein the elastomer is selected from at least one of a styrene elastomer, a silicone elastomer, or a methacrylate elastomer.
[0086] In some embodiments, the styrenic elastomer is at least one of a hydrogenated styrene and butadiene diblock copolymer, a hydrogenated styrene and butadiene triblock copolymer, a hydrogenated styrene and pentadiene diblock copolymer, and a hydrogenated styrene and pentadiene triblock copolymer;
[0087] The silicone elastomer contains at least one of the structural formula (13), the structural formula (14) and the structural formula (15):
[0088] In the structural formula (13), R is C1-C 12 A hydrocarbon group or -O-R1, R1 is C1-C 12 The hydrocarbon group;
[0089] In the structural formula (14), R is C1-C 12 A hydrocarbon group or -O-R1, R1 is C1-C 12 The hydrocarbon group;
[0090] In the structural formula (15), X is a mercapto group, an epoxy group, a hydroxyl group or a methoxy group;
[0091] The acrylic elastomer is a compound having the structural formula (16) and / or the structural formula (17):
[0092] In the structural formula (16), R1 is a C1-C5 alkyl group, and x is an integer of 1 to 100;
[0093] In the structural formula (17), R2 is a C1-C5 alkyl group, and y is an integer of 1-100.
[0094] In some embodiments, the resin composition further comprises 0.01 to 8 parts by weight of a catalyst, wherein the catalyst is selected from at least one of imidazoles, pyridines, organic phosphorus or metal salts. Preferably, the catalyst is selected from at least one of 4-dimethylaminopyridine, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, modified imidazole, zinc octanoate and triphenylphosphine.
[0095] In some embodiments, the resin composition further comprises 5-30 parts by weight of a flame retardant, wherein the flame retardant is selected from at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organosilicon flame retardant, and an organometallic salt flame retardant.
[0096] Preferably, the brominated flame retardant is selected from decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide;
[0097] The phosphorus flame retardant is selected from condensed phosphate esters, phosphoric acid, hypophosphite, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, (m is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphophanate-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene, modified phosphazene. Among them, the DOPO group is
[0098] More preferably, the flame retardant is a condensed phosphate ester, a hypophosphite or a bis-DOPO compound (ie, the aforementioned compound containing two DOPO groups).
[0099] In some embodiments, the resin composition further comprises 30 to 200 parts by weight of a filler, and the filler is selected from an inorganic filler, an organic filler or a composite filler. Among them, the inorganic filler is selected from at least one of silicon dioxide, aluminum hydroxide, aluminum oxide, talc, aluminum nitride, boron nitride, silicon carbide, barium sulfate, barium titanate, strontium titanate, calcium carbonate, calcium silicate, mica, and glass fiber powder; the organic filler is selected from at least one of polytetrafluoroethylene powder, polyphenylene sulfide powder, and polyether sulfone powder.
[0100] Preferably, the filler is spherical silica, alumina or aluminum hydroxide, more preferably spherical silica.
[0101] Furthermore, the filler is surface treated with a silane coupling agent, and the silane coupling agent is at least one of an aminosilane coupling agent, a carbon-carbon double bond-containing silane coupling agent, or an epoxy silane coupling agent.
[0102] Preferably, the silane coupling agent is selected from the group consisting of KBM-573 produced by Shin-Etsu Chemical Co., Ltd., Z-6883 produced by Dow Corning Corporation, KBM-1003 produced by Shin-Etsu Chemical Co., Ltd., and KBM-1403 produced by Shin-Etsu Chemical Co., Ltd.
[0103] The present invention also provides the use of the resin composition in prepregs, laminates, insulating films, insulating boards, copper-clad boards, circuit substrates and electronic devices, which are specifically described as follows:
[0104] The present invention also provides a prepreg, comprising a reinforcing material and the above-mentioned resin composition. The preparation method of the prepreg is: dissolving the resin composition with a solvent to prepare a glue solution, then immersing the reinforcing material in the above-mentioned glue solution, taking out the immersed reinforcing material and baking it at 100-180°C for 1-15 minutes; after drying, the prepreg is obtained.
[0105] The solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene and cyclohexane.
[0106] The reinforcing material is selected from at least one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fabrics. Preferably, the reinforcing material is glass fiber cloth; among the glass fiber cloth, open fiber cloth or flat cloth is preferably used; and the glass fiber cloth is preferably E glass fiber cloth, S glass fiber cloth, T glass fiber cloth, or Q glass fiber cloth.
[0107] In addition, when the reinforcing material is glass fiber cloth, the glass fiber cloth is chemically treated with a coupling agent to improve the interface bonding between the resin composition and the glass fiber cloth. The coupling agent is preferably an epoxy silane coupling agent or an amino silane coupling agent to provide good water resistance and heat resistance.
[0108] An embodiment of the present invention also provides a laminate, comprising a piece of the aforementioned prepreg and a metal foil disposed on at least one side of the prepreg; or comprising a composite sheet formed by overlapping a plurality of the aforementioned prepregs and a metal foil disposed on at least one side of the composite sheet.
[0109] The laminate is prepared by the following method: a metal foil is coated on one or both sides of a prepreg, or at least two prepregs are stacked to form a composite sheet, a metal foil is coated on one or both sides of the composite sheet, and the metal foil laminate is obtained by hot pressing. The pressing conditions of hot pressing are: pressing at 0.2-2MPa and 150-250°C for 2-4 hours.
[0110] Preferably, the metal foil is selected from copper foil or aluminum foil. The thickness of the metal foil is 5 micrometers, 8 micrometers, 12 micrometers, 18 micrometers, 35 micrometers or 70 micrometers.
[0111] An embodiment of the present invention further provides an insulating board, comprising at least one of the aforementioned prepreg sheets.
[0112] The embodiment of the present invention further provides an insulating film, comprising a carrier film and the above-mentioned resin composition coated thereon, and the heat resistance of the insulating film is significantly improved.
[0113] The insulating film is prepared by the following method: the resin composition is dissolved in a solvent to prepare a glue solution, the glue solution is then coated on a carrier film, and the carrier film coated with the glue solution is heated and dried to obtain the insulating film.
[0114] The aforementioned solvent is selected from at least one of acetone, butanone, methyl isobutyl ketone, N, N-dimethylformamide, N, N-dimethylacetamide, ethylene glycol methyl ether, propylene glycol methyl ether, benzene, toluene, xylene, and cyclohexane.
[0115] The carrier film is selected from at least one of PET film, PP film, PE film and PVC film.
[0116] An embodiment of the present invention further provides a circuit substrate, comprising one or more of the aforementioned prepreg, laminate, insulating plate, and insulating film.
[0117] An embodiment of the present invention further provides an electronic device, comprising the aforementioned circuit substrate; since the heat resistance of the circuit substrate is greatly improved, the safety of the electronic device is significantly improved.
[0118] The technical solution of the present application is further described below in conjunction with some specific synthesis examples and comparative examples.
[0119] Synthesis example 1
[0120] 1 mol of diallyl bisphenol A, 3 mol of 4-aminobenzocyclobutene, 0.5 g of zinc chloride and 400 g of toluene are added to a reaction bottle and stirred to obtain a mixed solution. The solution is heated to about 50°C and stirred evenly. During stirring, 2 mol of formaldehyde solution is added dropwise to the solution within 30 minutes, and the solution is heated and maintained at a temperature between 85°C and 90°C and reacted for 3 hours. After the reaction, the heating is stopped and the solution is allowed to stand for 20 minutes. After the solution is separated, the upper aqueous phase and a trace amount of emulsified product are removed. The solvent is recovered by heating and decompression (heating to 90°C and decompression to 90 mmHg) to obtain a diallyl bisphenol A type benzoxazine compound.
[0121] Synthesis example 2
[0122] 1 mol of diallylbisphenol methane, 3 mol of 4-aminobenzocyclobutene, 0.5 g of zinc chloride and 400 g of toluene are added to a reaction flask and stirred to obtain a mixed solution. The solution is heated to about 50°C and stirred evenly. During stirring, 2 mol of formaldehyde solution is added dropwise to the solution within 30 minutes, and the solution is heated and maintained at a temperature between 85°C and 90°C and reacted for 3 hours. After the reaction, the heating is stopped and the solution is allowed to stand for 20 minutes. After the solution is separated, the upper aqueous phase and a trace amount of emulsified product are removed. The solvent is recovered by heating and decompression (heating to 90°C and decompression to 90 mmHg) to obtain a diallylbisphenol methane type benzoxazine compound.
[0123] The chemical components and contents of the resin compositions of Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 1.
[0124] Table 1 Resin composition composition
[0125]
[0126]
[0127] Table 2 Materials
[0128]
[0129] The components of the resin compositions of Examples 1 to 6 and Comparative Examples 1 to 2 in Table 1 were dissolved in butanone, stirred and mixed, and then diluted to a glue solution with a solid content of 65 wt %; the E glass fiber cloth 2116 used as a reinforcing material was pretreated with an epoxy silane coupling agent, immersed in the above glue solution, taken out after infiltration, placed in a blast drying oven at 160° C., and baked for 3 to 6 minutes to obtain a semi-cured sheet.
[0130] Take two of the above-mentioned semi-cured sheets, cut them into 300×300 mm, and stack them into a composite sheet. Then, a low-profile electrolytic copper foil with a thickness of 12 μm is placed on both sides of the composite sheet, respectively. The composite sheet is placed in a vacuum hot press and hot-pressed for 1.5 h at a pressure of 1.5 MPa and a temperature of 220°C to obtain a copper-clad laminate. The specific performance tests are shown in Table 3.
[0131] The properties of the copper-clad laminates prepared in the above examples and comparative examples were tested as follows:
[0132] (1) Tg: DMA, heating rate 10°C / min, frequency 10 Hz;
[0133] (2) Water absorption (%): Tested according to IPC-TM-650 2.6.2.1 method;
[0134] (3) Dk and Df: Dielectric properties at 10 GHz were tested using the flat plate method in accordance with IPC-TM-650 2.5.5.9.
[0135] Table 3
[0136]
[0137] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0138] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present application. They are not intended to limit the scope of protection of the present application. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present application should be included in the scope of protection of the present application.
Claims
1. A resin composition, characterized in that By weight, it includes the following components: Benzoxazine resin: 1 to 80 parts by weight; Epoxy resin: 20-100 parts by weight; Curing agent: 5-50 parts by weight; The benzoxazine resin contains the following structural formula (1a) or structural formula (1b): Wherein, Ar is methylene, ethylene, 2. The resin composition according to claim 1, characterized in that The benzoxazine resin also includes a benzocyclobutenyl-free benzoxazine resin. Based on 100 parts by weight of the benzoxazine resin, the benzocyclobutenyl-free benzoxazine resin contains 10 to 80 parts by weight.
3. The resin composition according to claim 2, characterized in that The benzocyclobutenyl-free benzoxazine resin is selected from one or a combination of at least two of bisphenol A type benzoxazine resin, bisphenol F type benzoxazine resin, phenolphthalein type benzoxazine resin, dicyclopentadiene type benzoxazine resin, phosphorus-containing benzoxazine resin, diamine type benzoxazine resin or allyl benzoxazine resin.
4. The resin composition according to claim 2, characterized in that The benzocyclobutenyl-free benzoxazine resin is at least one of the following structural formulas: Wherein, R is vinyl, allyl, propenyl or methacrylate; Ar is methylene, ethylene, or no linking group; Wherein, Ar is methylene, ethylene, or no linking group; Wherein, R is vinyl, allyl, propenyl or methacrylate; Ar is methylene, ethylene, No linking group.
5. The resin composition according to claim 1, characterized in that The epoxy resin is selected from any one of dicyclopentadiene epoxy resin, carbon-carbon double bond epoxy resin, phosphorus-containing epoxy resin, isocyanate-modified epoxy resin, biphenyl epoxy resin, bisphenol A epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, epoxidized polybutadiene resin, naphthalene ring-containing epoxy resin, and bisphenol F epoxy resin, or a combination of at least two thereof.
6. The resin composition according to claim 1, characterized in that The epoxy resin is selected from at least one of the following structures: Wherein, m is an integer from 0 to 10; Wherein, n is an integer from 1 to 20; Wherein, p is an integer from 1 to 20; Wherein, n is an integer from 0 to 7, and R is H or -CH3; Wherein, X1 is H or a C1-C5 alkyl group; X2 is H or a C1-C5 alkyl group; Wherein, X1 is H or a C1-C5 alkyl group; wherein n is an integer from 0 to 7, and R is -CH2-, -C(CH3)2-, -SO2-, -O- or -Co-.
7. The resin composition according to claim 1, characterized in that The curing agent is selected from at least one of an amine curing agent, an active ester curing agent, a phenolic curing agent, an acid anhydride curing agent, a maleimide curing agent, and a cyanate curing agent.
8. The resin composition according to claim 7, characterized in that The amine curing agent is selected from at least one of diaminodiphenylmethane, diaminodiphenyl sulfone, diethylenetriamine, dicarboxyphthalimide, dicyandiamide or imidazole; The phenolic curing agent is selected from at least one of bisphenol A phenolic resin, phenol phenolic resin, naphthalene phenolic resin, biphenyl phenol phenolic resin, biphenyl phenol naphthol resin, and dicyclopentadiene phenol addition resin; The acid anhydride curing agent is selected from at least one of phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, hydrogenated phthalic anhydride, nadic anhydride or styrene-maleic anhydride; The cyanate curing agent is selected from at least one of bisphenol A cyanate, bisphenol F cyanate, bisphenol E cyanate, bisphenol M cyanate, DCPD cyanate, naphthalene cyanate, phenolic cyanate and biphenyl cyanate; The active ester curing agent is a compound having the following structural formula: Wherein, X is phenyl or naphthyl; j is 0 or 1; k is 0 or 1; and n represents a repeating unit, which is 0.25-1.
25.
9. The resin composition according to claim 1, characterized in that The invention also comprises 5 to 30 parts by weight of a flame retardant, wherein the flame retardant is selected from at least one of a bromine flame retardant, a phosphorus flame retardant, a nitrogen flame retardant, an organosilicon flame retardant and an organometallic salt flame retardant.
10. The resin composition according to claim 9, characterized in that The brominated flame retardant is selected from at least one of decabromodiphenyl ether, decabromodiphenyl ethane, brominated styrene or tetrabromophthalamide; The phosphorus-based flame retardant is selected from condensed phosphate esters, phosphoric acid, hypophosphite, phosphorus oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, (m is an integer from 1 to 5), 10-phenyl-9,10-dihydro-9-oxa-10-phosphophanate-10-oxide, tris(2,6-dimethylphenyl)phosphine, phosphazene, modified phosphazene, wherein the structure of the DOPO group is 11. Use of the resin composition according to any one of claims 1 to 10 in prepregs, laminates, insulating films, insulating boards, circuit substrates and electronic devices.
Citation Information
Patent Citations
Benzoxazine monomer containing benzocyclobutene and synthetic method and application thereof
CN102391201A
Benzocyclobutene functional groups-contained benzoxazine monomer and synthetic method and use thereof
CN102391202A
Low-dielectric unsaturated benzoxazine resin composition and preparation method thereof
CN112062908A
Poly(arylene ether) adhesive compositions
KR1020010114177A
Epoxy resin composition for build-up insulating film, insulating film formed therefrom, and multilayer printed circuit board having the same
US20140014402A1
Cited By
Benzoxazine compound, benzoxazine mixture, resin composition and application of resin composition
CN119390663A
Benzoxazine compound, benzoxazine mixture, resin composition, and application of resin composition
CN119390663B